FORMULATION AND EVALUATION OF FUROSEMIDE LIQUISOLID COMPACT - Jassim, Zainab E. (International Journal of Applied Pharmaceutics, 2017)
Objective: The purpose of this study was to enhance the dissolution pattern of the practically water-insoluble diuretic drug, furosemide through its formulation into liquisolid tablets. Methods: A mathematical model was used to formulate four liquisolid powder systems using polyethylene glycol 400 as a non-volatile water miscible liquid vehicle. The liquid loading factors of the vehicle were used to calculate the optimum quantities of carrier (Avicel PH 102) and coating materials (Aerosil 200) needed to prepare acceptably flowing and compactible powder mixtures and (R) ratio used was 25. The liquisolid tablets were evaluated for weight variation, percent friability, hardness, content uniformity, disintegration time and in vitro drug release profile. Drug and the prepared systems were characterized by fourier transform infrared spectroscopy (FTIR), differential scanning calorimetry (DSC) and powder x-ray diffraction (PXRD) studies. Results: The enhanced dissolution rate due to the increased wetting properties and the large available surface areas for dissolution were obtained in case of the liquisolid tablets. The selected optimal formulation (F2) of 50% drug concentration released 90% of its content during the first 10 min compared to 65% of DCT. FTIR studies revealed that there was no interaction between drug and polymers. DSC and PXRD indicated conversion of crystalline to amorphous form of furosemide.Â  Conclusion: The dissolution rate of furosemide can be enhanced to a great extent by liquisolid technique.